A case report of metastatic adenocarcinoma of the gingiva - Buddula Aravind (Wolters Kluwer Medknow Publications, 2009)
Localized gingival enlargement is often associated with specific systemic medication, abscess formation, trauma or reactive lesions. Scant literature is available reporting enlargement of gingiva due the metastasis of adenocarcinoma from lung. The case report presents a unique case of an adenocarcinoma in the lung metastasizing to the buccal and lingual interdental papillae of teeth numbering 34 and 35. A 72-year-old female was referred to the Mayo Clinic with a recent diagnosis of metastatic stage IV adenocarcinoma of the left lung presented with an abnormal mass located on the left posterior buccal keratinized tissue adjacent to teeth numbering 34-35. Biopsy of the lesion was performed for CK7, CK20, TTF-1 and p63. The tumor cells were positive for CK7 and TTF-1, and weakly positive for p63 suggesting a diagnosis of adenocarcinoma. The periodontist may be in the unique position to be the first oral health care provider to evaluate any biopsy suspicious intra-oral lesions.